Efeitos da restrição alimentar no desempenho de bovinos jovens confinados - Arrigoni, Mario de Beni [UNESP]; Vieira, Paulo de Figueiredo [UNESP]; Silveira, Antonio Carlos [UNESP]; Furlan, Luiz Roberto [UNESP]; Costa, Ciniro [UNESP]; Chardulo, Luis Arthur Loyola [UNESP]; Curi, Paulo Roberto [UNESP] (My University, 1998)
The objective of the study was to evaluate compensatory weight gain in the performance of young bulls submitted to feed restriction, in the initial phase of confinement and to study the economic viability of the utilization of three protein sources. Sixty six crossbred bulls Simental-Nelore, eight months old and averaging 220 kg of weight were submitted to three feeding programs in the growth phase that lasted 84 days. The feeding programs were ad libitum, restriction + raw soybean grains and restriction + toasted soybean grains, with a restriction level of 25% on average. In the finishing phase, with a 61 day duration, animals fed with each of the three diets mentioned above received two types of supplementary diets: raw soybean grains and poultry litter. There were no differences between final weights of animals in finishing phase, but the bulls submitted to the restriction had more weight gain per day and better food conversion than ad libitum animals, for both raw soybean grains and poultry litter. The conclusion was that the feeding restriction and consequent compensatory weight gain, presented advantages for feeding efficiency, by decreasing maintenance requirements, although final cost had been equivalent to ad libitum animals.

O trabalho objetivou avaliar as respostas do ganho compensatório no desempenho de animais mestiços jovens submetidos à restrição alimentar, na fase inicial de confinamento, e estudar a viabilidade econômica da utilização de três fontes protéicas. Foram utilizados 66 bovinos inteiros mestiços Simental-Nelore, com 8 meses e peso médio de 220±34,03 kg. Na fase de crescimento, com duração de 84 dias, os animais foram submetidos a três dietas alimentares: ad libitum (AL); restrição + soja crua (RSC) e restrição + soja torrada (RST), sendo o nível de restrição em torno de 25%. Na fase de terminação, com duração de 61 dias, os animais alimentados com cada uma das dietas citadas, receberam grãos de soja crus e cama de frango, como fonte suplementar de proteína. Os resultados mostraram que não houve diferenças entre os pesos finais dos animais, em fase de terminação. No entanto, os animais submetidos à restrição apresentaram maior ganho de peso diário e melhor conversão alimentar do que os ad libitum, em ambos os tratamentos, soja crua e cama de frango. Concluiu-se que a restrição alimentar com consequente ganho compensatório apresentou vantagens quanto aos índices de eficiência alimentar, por diminuir as exigências de manutenção, embora os custos finais tenham sido equivalentes aos dos animais ad libitum.
Effects of nutritional restriction on the performance in feedlot young bulls
Keywords: Crossbred Simental-Nelore; Feeding restriction; Animalia; Glycine max